Four new species of the subfamily Gryllacridinae (Orthoptera: Gryllacrididae) from China - Li, Miaomiao; Liu, Xianwei; Li, Kai (Zootaxa, 2016)
A taxonomic study of the subfamily Gryllacridinae is presented. Four new species belonging to two genera are described: Larnaca sinica sp. nov., Larnaca hainanica sp. nov.; Prosopogryllacris chinensis sp. nov., Prosopogryllacris incisa sp. nov.. A revised key and distributional data are given.